2022
DOI: 10.32604/cmc.2022.027293
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Internet Banking Adoption: An Application of Adaptive LASSO

Abstract: This research investigates a broad range of possible factors affecting the adoption of new technology in the banking industry using adaptive LASSO and a standard logit model. The research integrated the adoption of the innovation framework and the technology acceptance theory to develop a conceptual framework for the analysis. Primary data was collected from 400 bank customers in North Cyprus. Risk perception and other customerspecific factors such as perceived risk index and negative attitude toward new techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The adoption of digital banking services in Malaysia has been a topic of interest and research within the academic community (Akhter et al, 2020). Numerous studies have been conducted to investigate the factors that affect the adoption of online banking in Malaysia and to understand the customer's perspective on adopting digital banking services (Jenkins et al, 2022) Several studies have identified trust, privacy concerns, perceived security, and perceived usefulness as crucial factors influencing the adoption of digital banking services (Kurniasari, 2021;Chiu et al, 2017;Kazi & Mannan, 2013;Rotchanakitumnuai & Speece, 2003). Trust plays a crucial role in adopting digital banking services (Susanto et al, 2013).…”
Section: Adoption Of Digital Banking Servicesmentioning
confidence: 99%
“…The adoption of digital banking services in Malaysia has been a topic of interest and research within the academic community (Akhter et al, 2020). Numerous studies have been conducted to investigate the factors that affect the adoption of online banking in Malaysia and to understand the customer's perspective on adopting digital banking services (Jenkins et al, 2022) Several studies have identified trust, privacy concerns, perceived security, and perceived usefulness as crucial factors influencing the adoption of digital banking services (Kurniasari, 2021;Chiu et al, 2017;Kazi & Mannan, 2013;Rotchanakitumnuai & Speece, 2003). Trust plays a crucial role in adopting digital banking services (Susanto et al, 2013).…”
Section: Adoption Of Digital Banking Servicesmentioning
confidence: 99%
“…This is because women are more worried about their privacy and security while using the internet for financial transactions. Meanwhile, Jenkins, Hesami, and Yesiltepe (2022); Almutairi (2021); Fetu (2019); Serener (2018); Monisha et al (2017); Belay et al (2016) and Aslam et al (2011) found that clients with higher education level including either bachelor degree or post graduate degree as well as clients with upper and middle income level are more likely to use internet banking. Regarding age, it was noted that the majority of internet banking customers tend to be young.…”
Section: Introductionmentioning
confidence: 99%